Value chain analysis of the lanzones industry in the province of Camiguin - De La Plaza, Miriam A.; Posadas, Roger D. (Quezon City University of the Philippines Diliman, 2014)
Lanzones (Lansium domesticum corr.) is one of the fruits grown in the island province of Camiguin that is believed to have contributed to the economic development of the island not only in the production and trading business but also in terms of boosting the tourism industry. Every third week of October, lanzones festival is celebrated in the island. Activities include Agro-Industrial Fair where harvests of lanzones and oter agricultural crops in the island are being showcased. Being an important industry to the province, the lanzones industry needs a thorough study of how much more has to be done to develop its competitive advantage, thus, this research is being conducted. The value chain approach is becoming intensively used both by private sector agents as well as government and development agencies to both identify options for industrial development and implement development programs. Its particular attractiveness draws from, among other things, its capacity to deal with a new business environment prevalent in industrial development in the context of today's globalized markets. (UNIDO, 2009). The study aims to identify the existing actors, "the rules of the game" and the interrelationships among them. It also describes how the product are transformed, transported, packaged and marketed until it reaches the final consumer. It also describes how the actors are separated by time and space and how are the products valued as they pass from one link in the chain to the next. And lastly, recommend possible option to make the lanzones industry in the province of Camiguin innovative. Data gathering included primary data from the farmers, traders and other stakeholders. Secondary data were also obtained from other government offices such as Department of Agriculture, Department of Trade and Industry and the Department of Tourism with regards to production volume and sales, influx of tourists during the lanzones festival month and their respective programs towards lanzones industry development. Michael Porter provided a value chain framework that included the primary and support activities in the chain while the UNIDO provided a step by step approach on how will it be conducted. Both provided the framework on how this study was conducted. The Provincial Government of Camiguin through the Provincial Agriculture Office and with the assistance of the Department of Agriculture was instrumental in the development of the industry through the following interventions : establishment of lanzones nurseries, provision of planting materials through the Plant now Pay Later (PNPL) program, establishment of demo farms, ans lately the packaging materials of fresh lanzones fruits. The Department of Science and Technology through the Philippine Council for Agriculture and Aquamarine Resources Research and Development (PCAARRD) identified lanzones as a commodity for the Science and Technology Based Farm which supported a Magsasaka Siyentista enhance his cultural practices on proper irrigation and fertilization. The Department of Trade and Industry initiated the clustering approach in year 2001 and assisted in organizing the Lanzones Traders Association but was not sustained due to the shift of priority from the Lanzones Industry Cluster to a broader industry which is the Tourism Industry. However, assistance in the promotion and marketing of products is still part of the DTI's regular program. Other agencies such as Philippine Coconut Authority, Department of Agrarian Reform, Department of Labor and Employment and The Department of Tourism also assisted in the production and marketing activities. Lanzones trees are grown naturally all over the island. The year 2013 was the 34th Lanzones Festival in the island but only about 10 years ago that formal lanzones farming was considered to be a serious business among the 25 farmers surveyed. Basically, the Camiguin lanzones were sold in local market, a large bulk were sold in Mindanao, a few reaches the market in the Visayas and Luzon and none was sold in the foreign market. The farmer-respondents preferred to sell their products to local buyer-wholesalers through the arrangement of "pakyaw" system (60 percent). These local buyer-wholesalers sell them to hotels and resorts, retailers and ship the products outside the island. These type of buyers assume the expenses during harvesting and marketing of fruits. This kind of arrangement remove the farmers many of the risks involved in the fruiting, harvesting and marketing. This system may be both an advantage and disadvantage to the farmers.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Fruit trade -- Philippines; Economic development; Value chain analysis; Lanzones industry